A novel approach to dynamic signature verification using sensor-based data glove - N.S., Kamel (2009)

(untitled)
Data glove is a new dimension in the field of virtual reality environments, initially designed to satisfy e stringent requirements of modem motion capture and animation professionals. In this study we try to shift the implementation of data glove from motion animation towards signature verification problem, making use of the offered multiple degrees of freedom for each finger and for the hand as well. We used an SVD-based technique to extract the feature values of different sensors' locating on corresponding fingers in the signing process and evaluated the results for writer authentication. The technique is tested with large number of authentic and forgery signatures using data gloves with 14, 5 and 4 sensor and shows a significant level of accuracy with 2.46-5.0% of EER. Â© 2009 Science Publications.